Coaching Fast–Coaching Slow: Applying Positive Psychology, Behavioral Economics and Neuroscience to Leadership Coaching - Forbes Jr., Raymond L. (Advances in Social Sciences Research Journal, 2025)
What can the rapidly expanding esoteric field of Neuroscience or Brain Science possibly offer the very pragmatic “hands on” Leadership Coaching profession? How can research findings from the fields of Positive Psychology and Behavioral Economics be productively used by the practicing Leadership Coach? Does a choice of coaching style and speed of interaction actually matter in producing successful coaching outcomes? This paper will explore answers to these questions, discuss some of the relevant research and offer practical applications and insights that can be used by the practicing leadership coach to become more effective. The intent of this work is to help bridge the gap between cognitive neuroscience, positive psychology, and behavioral economics and the application of useful tools for the leadership coach. In particular, the body of work and insights of Nobel prize-winning Israeli-American Psychologist Daniel Kahneman will be highlighted. Included in the paper is a definition of both fast and slow coaching, potential areas of neuroscience research support, examples of fast and slow techniques, integration of the two modes, implications for research, and a closing summary.